2007
DOI: 10.1155/2007/63624
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Meningitis during Pregnancy: A Case Report and Review of Literature

Abstract: Background. Bacterial meningitis is a medical emergency for which prompt diagnosis and treatment are imperative to reducing the rate of death and long-term neurologic compromise. Few cases of meningitis have been reported during pregnancy, many of which had devastating outcomes for mother, neonate, or both. Case. A 38-year-old multigravida at 35 weeks of gestation presented with mental status changes, fever, and preterm contractions. Lumbar puncture revealed gram positive cocci consistent with S. pneumoniae. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 5 publications
3
20
0
1
Order By: Relevance
“…Patients in our cases-series were relatively old compared with previous studies of pneumococcal meningitis during pregnancy [7][8][9][10][11][12][13][14][15][16][17]: four of six women were over 35 years. This is probably explained by the higher age of childbearing in the Netherlands [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients in our cases-series were relatively old compared with previous studies of pneumococcal meningitis during pregnancy [7][8][9][10][11][12][13][14][15][16][17]: four of six women were over 35 years. This is probably explained by the higher age of childbearing in the Netherlands [33].…”
Section: Discussionmentioning
confidence: 99%
“…Six of the 25 cases of pneumococcal meningitis during pregnancy were included in a previous review study [7], and 15 were reported in a Nigerian case series performed from 1958 to 1962 (Table 2) [15]. Combining these patients with Landrum [7] Bakaya [17] Vives [13] Felisati [16] Iinuma [14] Present study The patient had a miscarriage shortly before admission and died on the 16th day of admission.…”
Section: Review Of the Literaturementioning
confidence: 94%
See 2 more Smart Citations
“…Maternal meningitis due to S. pneumoniae during pregnancy and postpartum is very rare (2–9). In this case report, we describe a patient who developed fever and mental status changes during the postpartum period and was subsequently diagnosed with maternal pneumococcal meningitis complicated by endocarditis.…”
Section: Introductionmentioning
confidence: 99%